East Java Economic Analysis on Sectoral and Regional Linkages (Inter Regional Input-Output Analysis) - Tika Meilaningsih; Widya Yuniastuti (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2022)
East Java's economic recovery due to the Covid-19 pandemic is no better than the national economic recovery. In 2020, East Java's economic growth contracted by 2.33 percent (y-on-y), deeper than the national economy which contracted 2.07 percent (y-on-y). Moreover, when the national economy began to recover and grew to 3.69 percent (y-on-y) in 2021, East Java's economic growth only increased by 3.57 percent (y-on-y). These conditions indicate that the East Java economy is in need of appropriate and comprehensive policies to support the acceleration of economic recovery. Viewed from the high contribution of the Manufacturing Industry (C) sector to East Java's GRDP in recent years, this sector has the opportunity to be encouraged to grow. However, GRDP has not been able to explain the interlinkages between economic sectors that occur in a region. By using the 2016 IRIO table, input-output analysis can provide more complete and comprehensive information covering inter-sectoral and inter-regional linkages that cannot be captured only from GRDP figures. The results showed that the Manufacturing Industry (C), Electricity and Gas Procurement (D), and Information and Communication (J) sectors were the key sectors in East Java. These key sectors, especially Information and Communication (J) and Manufacturing Industry (C), have the potential to boost output in East Java as a whole. Spatially, seen from the input transaction pattern, among others, East Java transactions are dominated by transactions with other provinces on the island of Java, some provinces on the island of Kalimantan, as well as provinces in Eastern Indonesia (KTI), namely Bali-Nusa Tenggara, Sulawesi, and Maluku- Papua. The demand for intermediate input from KTI, especially Bali-Nusa Tenggara, is dominated by DKI Jakarta and East Java. Seeing the location of East Java which is closer to the provinces in KTI, makes it an opportunity to increase the supply of East Java's output to KTI.